Serum miR‐195‐5p is upregulated in gestational diabetes mellitus - Wang, Jianping (J Clin Lab Anal, 2020)
BACKGROUND: Gestational diabetes mellitus (GDM) is defined as varying degrees of glucose intolerance with an onset or first recognition during pregnancy in women without previously diagnosed diabetes. Accumulating evidence indicates that miRNAs exert crucial roles in the pathogenesis and development of diabetes, including GDM. In the present study, we aimed to determine the clinical performance of miR‐195‐5p in GDM. METHODS: First, the miR‐195‐5p expressions in serum samples from healthy pregnant women and women with GDM at 25 weeks pregnancy were detected using real‐time polymerase chain reaction (RT‐qPCR). Then, receive characteristic (ROC) curve was used to determine the diagnostic value of miR‐195‐5p in GDM. Finally, the correlation analysis of miR‐195‐5p expression with related clinicopathological factors was carried out to determine the clinical value of miR‐195‐5p in GDM. RESULTS: In this study, we found that miR‐195‐5p expression was significantly increased in serum samples from GDM patients as compared with that in healthy pregnancies. Furthermore, miR‐195‐5p might be a putative biomarker for GDM diagnosis with an area under the curve (AUC) of 0.8451; the cutoff value was 1.598, sensitivity was 73.69%, specificity was 96.85%, accuracy was 81.26%, and Youden index was 70.54%. Expression of miR‐195‐5p was positively associated with fasting plasma glucose, one‐hour plasma glucose, and two‐hour plasma glucose. CONCLUSION: miR‐195‐5p might function as a putative diagnostic biomarker for GDM and contribute to identifying at‐risk mothers in pregnancy.